Pathological features determinants in the evolution of breast cancer - Rivas Gonzáles, Mauro (1967)
Of the various objective factors that have been evaluated and could be used to predict a particular case that has just been treated surgically , has been considered : the size of the primary tumor nodule , the presence or absence of nodal metastases , type of neoplasia , degree of cell differentiation, degree of lymphoplasmacytic infiltration and fibrosis. From the above elements we found that the degree of fibrosis and the degree of cell differentiation does not appear to be useful because no significant differences between the group of patients alive and dead by the group of neoplasia. In other words, these factors do not appear to influence the course of the disease . Instead, the following factors: primary tumor size , degree of lymphoplasmacytic infiltration of the tumor and lymph node metastasis is if valuable elements in the prediction of evolution. In short, one could argue that the smaller is the primary tumor nodule has no axillary metastases and marked lymphoplasmacytic reaction exists in the primary tumor, the prognosis of the case will be favorable. Conversely, the larger the primary tumor, axillary metastases and there is little or no reaction linfoplasmocitaria the primary tumor , the chances of survival are restricted. The considerations just made in the previous paragraph refer to cases treated with the same procedure , at the time it was made (1952-1953) , was considered the treatment of choice for breast cancer (radical mastectomy ) ; currently no reason to think that the treatment of breast cancer that has extended to the internal mammary chain ( ultra-radical mastectomy ) , the validity of the above previous paragraphs no longer take place.